In silico screening and molecular docking study of selected amaryllidaceae alkaloids as potential inhibitors of SARS-COV-2 RNA-Dependent RNA Polymerase (RDRP) - John Christian C. De Guzman. 4 0 16; 5 (2022)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2